COVID-19 and Entrepreneurship Entry and Exit: Opportunity Amidst Adversity - Vladimir Otrachshenko; Olga Popova; Milena Nikolova; Elena Tyurina (Institute of Labor Economics (IZA), 2022)
We theoretically and empirically examine how acquiring new skills and increased financial worries influenced entrepreneurship entry and exit intentions during the pandemic. To that end, we analyze primary survey data we collected in the aftermath of the COVID-19's first wave in Russia, which has had one of the highest COVID-19 infection rates globally. Our results show that acquiring new skills during the pandemic helps maintain an existing business and encourages start-ups in sectors other than information technology (IT). For IT start-ups, having previous experience matters more than new skills. While the pandemic-driven financial worries are associated with business closure intentions, they also inspire new business start-ups, highlighting the creative destruction power of the pandemic. Furthermore, preferences for formal employment and remote work also matter for entrepreneurial intentions. Our findings enhance the understanding of entrepreneurship formation and closure in a time of adversity and suggest that implementing entrepreneurship training and upskilling policies during the pandemic can be an important policy tool for innovative small business development.
Keywords: E24; J24; L26; P20; 330; entrepreneurship intentions; COVID-19; business closure; information technology (IT); business entry; self-employment; Russia